OPTIMIZATION OF EXERCISE THERAPY TO INCREASE THORACIC CAGE EXPANSION IN TUBERCULOUS MENINGITIS CASES - Ahmad Akbar Pamungkas; Dinda Dwi Anggari; Isna Rahma Septiana; Enitha Gamganora; Amalga Tri Gusta Nanda; Arshy Prodyanatasari; Whida Rahmawati (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
Tuberculous meningitis (TBM) is the most severe form of tuberculosis, causing significant neurological impairment and respiratory complications in children. The novelty of this research (a) lies in demonstrating the application of a simple, practical physiotherapy protocol within a resource-limited healthcare setting. The objective of this study (b) is to report the effectiveness of this physiotherapy intervention for a 9-year-old boy with TBM. The methods employed (c) included a series of interventions over three sessions, comprising positioning to optimize ventilation and prevent pressure sores, passive breathing exercises to support lung capacity, and passive mobilization to maintain joint range of motion and control spasticity. Evaluation was based on thoracic expansion measurements, the Glasgow Coma Scale (GCS), and spasticity assessment. The empirical results (d) indicated notable clinical improvements, including increased thoracic expansion, enhanced level of consciousness, and stabilized spasticity. The study's implications (e) confirm that a consistent regimen of straightforward physiotherapy techniques can significantly support the recovery process of pediatric TBM patients, offering a viable and accessible supportive care model for hospitals with constrained resources.